Unique spectral features of DNA infrared bands of some microorganisms. Issue 5 (2009) - Ahmed Ahmed, M. Khalique M. Khalique; Amiama Amiama, Frank Frank; Sealy Sealy, Earl A. Earl A.
Abstract : Half dozen microorganisms ( Serratia marcescens, Klebsiella pneumonia, Staphylococcus aureus, Bacillus subtilis, Mycobacterium smegmatis and Saccharomyces cerevisiae ) were cultivated, and their infrared spectra were recorded in the attenuated total reflection mode. Both the intensities and frequencies of the B-DNA and Z-DNA bands in the spectral region of 1250–900 cm –1 were found to be different for different microorganisms. We suggest that characterization and identification of microorganisms may be possible through analysis of their DNA bands only without the analysis of the full range (4000–700 cm –1 ) of their infrared spectra.